Key success factors in establishing end-of-life vehicle management system: a primer for Malaysia - Raja Mamat, Tengku Nur Azila; Mat Saman, Muhamad Zameri; Sharif, Safian; Simic, Vladimir (Elsevier, 2016)
In Malaysia, end-of-life vehicles are not properly managed. Their number keeps growing, as reflected by the increasing number of produced and registered vehicles every year. Improper management of end-of-life vehicles endangers environment and social life in Malaysia. Excessive water, air and soil pollution are among the primary effects of improper end-of-life vehicle management. These negative impacts have led to an initiative to develop a framework for establishing end-of-life vehicle management system in Malaysia. A set of preliminary factors and underlying items have been identified from previous research efforts. Then, a large survey, with 300 respondents comprising of vehicle manufacturers and distributors, part dealers, and end-of-life vehicle collectors; and high response rate, was conducted. Responses of the survey were factor-analysed using IBM SPSS Statistics version 20. As a result, the eight success factors namely management responsibility, performance management, capacity management, resource management, stakeholder responsibility, education and awareness, improvement and awareness, and cost management in implementing end-of-life vehicle management system in Malaysia and 33 underlying items are identified and thoroughly discussed. By conducting reliability analysis, all eight success factors are determined to be reliable. Linear relationship among the factors is then confirmed using structural equation modeling. Upon confirmation, the proposed framework containing factors and items, can be valuable for supporting authorities in establishing end-of-life vehicle management system not only in Malaysia, but also in other countries without proper end-of-life vehicle management system.